THE ABILITY OF STUDENTS’ CONCEPTUAL UNDERSTANDING IN COMPLETING STORY PROBLEMS ON MATHEMATICS - Mayasari, Dian; Habeahan, Nova Lina Sari (Jurnal Pendidikan Matematika dan IPA, 2021)
This study aims to describe the ability of students to understand concepts in solving story problems. The research subjects were 28 grade VII students of SMP Negeri 8 Merauke. Data collection techniques were carried out in tests of students' abilities in understanding concepts and unstructured interviews. The test used to measure the concepts is in the form of description questions and 4 questions with integer operation material on the story problem. From the data analysis, it was concluded that the students' ability at high ability could master the 6 indicators of concept understanding, students in the moderate category mastered 5 indicators of concept understanding, students in the low category mastered 4 indicators of conceptual understanding. It can be concluded that the students' concept understanding ability is in the medium category.